Zacharias Frankel’s Conception of the Septuagint in Context - Louw, Theo A. W. van der (Textus, 2021)
Zacharias Frankel had a very low opinion of the abilities of the LXX translators, the quality of their work and the ensuing textual transmission. He considered the Septuagint only useful as a testimony to help prove the antiquity of the halakah, a notion with apologetic value. Methodologically, he conceptualized the genesis of the Greek Pentateuch through the theories of contemporary historical criticism. His monographs on the Septuagint display great continuity with early modern scholarship. This also holds true for the assumption that the Septuagint reflects Jewish interpretation, and the notion of five translators/editors for the Greek Pentateuch. Frankel’s works were considered important, but his innovations, viz. the insistence that all Jewish exegesis was Palestinian in origin and his rejection of textual criticism, were accepted by few and rejected by most scholars, Jews and Christians alike. Frankel’s boldness and his use of German helped to keep his ideas on the scholarly agenda.